Retrospective analysis of a surgical innovation using the IDEAL framework: radical cystectomy with epidural anaesthesia. (April 2017) - Gerullis, Holger; Ecke, Thorsten H.; Barski, Dimitri; Bantel, Carsten; Weyland, Andreas; Uphoff, Jens; Jansen, Thomas; Wawroschek, Friedhelm; Winter, Alexander
Objectives: To retrospectively analyse experience of radical cystectomy using spinal/epidural anaesthesia and to classify this method using the IDEAL criteria. Methods: Data from patients who had undergone radical cystectomy using spinal/epidural anaesthesia were evaluated retrospectively, focusing on clinical data, intraoperative and perioperative parameters and postoperative complications. Current literature reporting on this technique was reviewed and, together with the present study, evaluated according to the IDEAL recommendations. Results: Three male patients aged 66–79 years who had undergone radical cystectomy with epidural anaesthesia were identified. The operating time ranged from 159–261 min and only minor complications occurred. Between 2013 and 2015, three published studies reported experiences with radical cystectomy with epidural/spinal anaesthesia; one was prospective and two were retrospective in nature and they included a total of 55 patients. According to the IDEAL classification, the present study corresponds to stage 1 (idea) and overall the surgical technique can be ranked as stage 2a (development). Conclusions: Radical cystectomy with epidural anaesthesia is feasible and applicable for those who are not fit for general anaesthesia. The present study confirmed the functional results of this technique, which can be classified as IDEAL stage 2a on the basis of published studies.